Feasibility of Direct Utilization of Biomass Gasification Product Gas Fuels in Tubular Solid Oxide Fuel Cells for On-Site Electricity Generation - Chen, Kongfa; Zhang, L.; Ai, Na; Zhang, Shu; Song, Yao; Song, Yuncai; Yi, Qun; Li, Chun-Zhu; Jiang, San Ping (American Chemical Society, 2016)
Biomass is one of the most abundant and cheap renewable energy sources, and gasification product gases from the pyrolysis process of biomass, such as mallee wood and wheat straw, contain typically 20-27% H2 and a small amount of CO and CH4 (8-13%). Here, preliminary results on the performance of Ni/Y2O3-ZrO2 cermet anode-supported tubular solid oxide fuel cells (SOFCs) for the electricity generation from gasification product gases are presented. Two product gases derived from mallee wood and wheat straw are used as the fuels. The tubular SOFCs deliver a maximum power density over 576 mW cm-2 at 800 °C, close to the power density based on the equivalent amount of pure H2 or CH4 fuel. The power density is affected by the flow rate of product gas, but there are no significant differences of power output among the product gas sources used. However, the cell performance decreases gradually, and the degradation in the electricity generation performance of the tubular SOFC is most likely due to the presence of impurities, such as sulfur- and chlorine-containing compounds in the biomass feedstock. The results demonstrate the feasibility of the gasification product gas-fueled SOFCs for the on-site electricity generation, and the deterioration effect of impurities could be mitigated by cleaning the product gases or developing the contaminant-tolerant electrodes.